Hydrogen Peroxide Accumulation in the Choroid During Intermittent Hypoxia Increases Risk of Severe Oxygen-Induced Retinopathy in Neonatal Rats - Beharry, Kay D. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. Extremely low gestational age neonates (ELGANs) requiring oxygen therapy often experience frequent episodes of intermittent hypoxia (IH) and are at high risk for severe retinopathy of prematurity (ROP). Using an established model for oxygen-induced retinopathy (OIR), we examined the hypothesis that there is a critical number of daily brief IH episodes which will result in irreversible retinal oxidative damage. METHODS. Newborn rats were exposed to increasing daily clustered IH episodes (12% O(2) with 50% O(2)) from postnatal day (P) 0 to P7 or P0 to P14, or placed in room air (RA) until P21 following 7- or 14-day IH. RA littermates at P7, P14, and P21 served as controls. A group exposed to constant 50% O(2) (CH) served as a second control. Blood gases, eye opening at P14, retinal, and choroidal oxidative stress and lipid peroxidation (8-isoPGF(2α)), oxidants (H(2)O(2)) and antioxidants (catalase and SOD), retinal pathology (adenosine diphosphatase (ADPase)-stained retinal flatmounts), and mitochondria-related genes were assessed. RESULTS. pO(2) levels were higher with increasing IH episodes and remained elevated during the reoxygenation period. High SO(2) levels were associated with most severe OIR. Levels of all measured biomarkers peaked with six IH episodes and decreased with 8 to 12 episodes. H(2)O(2) accumulated in the choroid during the reoxygenation period with irreversible retinal damage. CONCLUSIONS. Our data suggest that six is the maximum number of IH episodes that the retina can sustain. Accumulation of H(2)O(2) in the choroid may result in high levels being delivered to the entire retina, ultimately resulting in irreversible retinal oxidative damage.